"An Evaluation of the Predictive validity of Admission Criteria for Teacher Traininq in Ethiopia" - Belai, Teferra (The Ethiopian Journal of Education, 2024)
The purpose or this study was to examine the extent to which admission criteria for Teacher Training Institutions (TTI) in Ethiopia (l .e. , ESLCB GPA, Community Participation score, Interview score, and Teaching experience Score) are predictive or s uccess in TTI academic performance indepndently of each other as independently or sex, year or completion or secondary education and field attended in the high school.